Exclusion of pulmonary embolism using C-reactive protein and D-dimer - Aujesky, Drahomir; Hayoz, Daniel; Yersin, Bertrand; Perrier, Arnaud; Barghouth, Ghassan; Schnyder, Pierre; Bischof-Delaloye, Angelika; Cornuz, Jacques (Thrombosis and Haemostasis, 2003)
Our goal was to evaluate the diagnostic utility of C-reactive protein (CRP) alone or combined with clinical probability assessment in patients with suspected pulmonary embolism (PE), and to compare its performance to a D-dimer assay. We conducted a prospective study in which we performed a common immuno-turbidimetric CRP test and a rapid enzyme-linked immunosorbent assay (ELISA) D-dimer test in 259 consecutive outpatients with suspected PE at the emergency department of a teaching hospital. We assessed clinical probability of PE by a validated prediction rule overridden by clinical judgment. Patients with D-dimer levels ≥ 500 µg/l underwent a work-up consisting of lower-limb venous ultrasound, spiral computer-ized tomography, ventilation-perfusion scan, or pulmonary angiography. Patients were followed up for three months. Seventy-seven (30%) of the patients had PE.The CRP alone had a sensitivity of 84% (95% confidence interval [CI).: 74 to 92%) and a negative predictive value (NPV) of 87% (95% CI: 78 to 93%) at a cutpoint of 5 mg/l. Overall, 61 (24%) patients with a low clinical probability of PE had a CRP < 5 mg/l. Due to the low prevalence of PE (9%) in this subgroup, the NPV increased to 97% (95% CI: 89 to 100%). The D-dimer (cutpoint 500 µg/l) showed a sensitivity of 100% (95% CI: 95 to 100%) and a NPV of 100% (95% CI: 94 to 100%) irrespective of clinical probability and accurately rule out PE in 56 (22%) patients. Standard CRP tests alone or combined with clinical probability assessment cannot safely exclude PE.
Keywords: Pulmonary embolism; C-reactive protein; D-dimer; clinical probability assessment